Estudo de transformadores trifásicos/heptafásicos aplicados a retificadores 14 pulsos com alto fator de potência - Nascimento, Guilherme Antunes do (2013)
This paper presents a less studied rectifier topology to control the harmonic disturbances it may cause to the system it is connected to. Didactically, the text covers some important power quality standards, gives a brief explanation on transformers and rectifiers of different number of phases. In order to obtain a 14 pulses rectifier, a three to seven phase transformer was studied and designed. It was then presented the modeling of the rectifier configuration. After the definition of these elements, a simulation of the system was made in order to check the operation of all theoretical study. After assembly and testing of the transformer-rectifier assembly, the paper presents a conclusion, comparing the theory, the standards and other circuit types to the equipment studied.